2007
DOI: 10.1177/1073191107305570
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric and Structural Analysis of the MMPI-2 Personality Psychopathology Five (PSY-5) Facet Subscales

Abstract: The Personality Psychopathology Five (PSY-5) is a model of personality psychopathology assessed in adult populations with a set of Minnesota Multiphasic Personality Inventory-2 (MMPI-2) scales. The authors examine the reliability and validity of recently developed lower-order facet subscales for each of these five domains, with an emphasis on structural invariance, using both confirmatory factor analysis (CFA) and exploratory factor analysis (EFA). MMPI-2 protocols completed by psychiatric patients (N = 693) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…Although new to the DSM’s framework for diagnosing PD, these broad dimensions are rooted in the scientific literature associated with the Big-Five/Five-Factor Model of personality (Krueger, Eaton et al, 2011; Widiger & Simonsen, 2005) and are recognizable as maladaptive variants of these normative traits (Wright et al, in press). Additionally, they build upon prior successful attempts to operationalize maladaptive variants of these dimensions, such as the Personality Psychopathology-5 (Arnau, Handel, & Archer, 2005; Harkness, Finn, McNulty, & Shields, in press; Harkness & McNulty, 1994; Harkness, McNulty, & Ben-Porath, 1995; Quilty & Bagby, 2007; Wygant, Sellbom, Graham, & Schenk, 2006). …”
Section: Proposed Changes To Pd Section In Dsm-5mentioning
confidence: 99%
“…Although new to the DSM’s framework for diagnosing PD, these broad dimensions are rooted in the scientific literature associated with the Big-Five/Five-Factor Model of personality (Krueger, Eaton et al, 2011; Widiger & Simonsen, 2005) and are recognizable as maladaptive variants of these normative traits (Wright et al, in press). Additionally, they build upon prior successful attempts to operationalize maladaptive variants of these dimensions, such as the Personality Psychopathology-5 (Arnau, Handel, & Archer, 2005; Harkness, Finn, McNulty, & Shields, in press; Harkness & McNulty, 1994; Harkness, McNulty, & Ben-Porath, 1995; Quilty & Bagby, 2007; Wygant, Sellbom, Graham, & Schenk, 2006). …”
Section: Proposed Changes To Pd Section In Dsm-5mentioning
confidence: 99%
“… 1. Attempts have been made to develop PSY-5 scale facets (e.g., Arnau, Handel, & Archer, 2005), but these do not hold up structurally (Quilty & Bagby, 2007). …”
mentioning
confidence: 99%
“…More research is needed to test their utility, for example, because the internal consistency of some facets is unacceptably low (Graham 2006). In this regard, Quilty and Bagby (2007) found that the reliability and discriminability of the subscales were mostly inadequate. In terms of forensic application, Ben-Porath (2006) described his research showing relevant empirical correlates of the PSY-5 scales in a pretrial forensic assessment sample (Petroskey et al 2003).…”
Section: Criticisms Of the Dsm-iv Approach To Personality Disordermentioning
confidence: 90%